Growth and metabolic consequences of growth hormone treatment in prepubertal short normal children. Issue 3 (September 1994) - McCaughey, E S; Mulligan, J; Voss, L D; Betts, P R
Abstract : Growth and the metabolic effects of growth hormone were monitored in a randomised, controlled group of 41 short, normal, prepubertal children. The treated group received daily injections of growth hormone as Genotropin (Kabi Pharmacia) 30 IU/m2/week. Fifteen children in the treated group (21 children) have completed three years of treatment, have grown significantly more than 14 (of 20) untreated children, and have a significantly greater adult height prediction. They do, however, remain leaner (body fat 13.5% in the treated group, 18% in the untreated group) and relatively hyperinsulinaemic (insulin 66.7 pmol/l in the treated group, 44.5 in the untreated group) after three years compared with untreated children. Although growth hormone appears to improve the height potential of prepubertal short normal children, the long term outcome is still uncertain.